Elemental affinity for siderite found in a Japanese paddy subsoil. Issue 2 (4th March 2017) - Togami, Kazuki; Miura, Kenzo; Ito, Kumiko; Kanno, Hitoshi; Takahashi, Tadashi; Nanzyo, Masami
ABSTRACT: Siderite (FeCO3 ), a type of carbonate mineral, is very occasionally recognized as a nodule in anoxic soils and sediments. During siderite formation, elements are expected to be accumulated or excluded between siderite and bulk soil. Therefore, we verified the affinity of 40 elements for siderite found in the gley horizon of a smectite-rich paddy field in northeastern Japan from the elemental concentration of the soil and the siderite dissolved in 2.88 mol L −1 hydrochloric acid (10% HCl). The concentration ratio of the target element of the soil to the siderite was expressed by the product of the dimensionless R0 value and ratio of titanium (Ti) concentration of the soil to the siderite (Csiderite /Csoil ) = R0 (Tisiderite /Tisoil ). The affinity of each element for the siderite was analyzed by comparing the R0 values. In comparison with Ti used as the reference element, P, Cr, Co and Mo were accumulated (R0 > 1.0), and alkali metals, such as Li, Na and K, and chalcophile elements, such as Cu, Zn, Cd and Pb, tended to be equal or excluded from the siderite (R0 ≦1.0). Of the group 2 elements, Ca, Sr and Ba were accumulated, while Mg was excluded. The affinity of Mn for siderite exceeded that of Fe as the main component of the siderite, which reflects the fact that siderite was formed in a fresh water condition. The siderite size did not influence the elemental affinity. Observation of micromorphology using a scanning electron microscope showed that the siderite nodules were aggregations of siderite particles and clays, suggesting that the siderite grew by taking in clay around it. The rare earth element (REE) distribution pattern showed a tendency not to increase linearly but to increase with forming a concave curve at the intervals of the four elements with the increase of atomic number (i.e. tetrad effects). Although these findings are from the lower horizons of anoxic soils, the elemental affinity for siderite of this study is useful in order to elucidate the complex elemental dynamics in the anoxic environment.